Proceedings of the 2nd International Workshop in Applied Probability / IWAP 2004 - Koutras M V; University Of Piraeus (2004)
On the Waiting Time for the First Sucess Run, Exponential Behavior in Risk Theory, Estimation in Window-Censored Semi-Markov Processes, Random Sperner Systems, The Duration of a Sequence of Epidemics, Vertical Uniform Random Sampling, Non Parametric Methods of Inference for Finite-State and Inhomogenous Markov Processes, Developments in Discrete Frailty Models, Poison Process Approximation for Palindromes in DNA, On Transient Analysis of Queues with Poison Input Stream, Non-Homogeneous Semi-Markov Reliability Transition Credit Risk Models, Multivariate Karhunen-Loeve Decompositions and Statistical Applications, Recent Advances in Scan Statistics, Time Series Analysis by Higher Order Crossings, Results for the NK Model, Modes of Extinction, Motif Distribution in DNA Sequences, Symmetry Analysis of Refraction Data, Author Index.